We cannot empathize with what we do not recognize: Perceptions of structural versus interpersonal racism in South Africa - Fourie, Melike M.; Moore-Berg, Samantha L. (Frontiers in Psychology, 2022)
Recent research suggests holding a structural, rather than interpersonal, understanding of racism is associated with greater impetus to address racial disparities. We believe greater acknowledgment of structural racism also functions to mitigate against empathic failures in response to structural injustices. Given South Africa’s situatedness as a country characterized by historical racialized oppression and continuing unjust legacies, it is appropriate to examine these ideas there. Across three studies, we tested the hypotheses that members of advantaged groups’ perspective taking and empathic concern may be compromised in response to people challenging the unequal status quo, and that a priori perceptions about the impact of structural (vs interpersonal) racism may mitigate or exacerbate such empathic failures. In Study 1, a national sample of White South Africans (n = 195) endorsed perceptions of interpersonal racism more readily than perceptions of structural racism, and they expressed high levels of competitive victimhood for perceived anti-White structural racism. Studies 2 (n = 138) and 3 (n = 85) showed that White participants at a historically White university responded with impaired perspective taking and intergroup empathy bias in response to people challenging structural disparities. Finally, reduced recognition of continuing structural racism predicted greater intergroup empathy bias, which, in turn, was associated with reduced willingness to engage in intergroup discussions about past harm (Study 3). We propose that greater acknowledgment of structural racism is necessary not only to surmount intergroup empathic failures, but also to transcend the socioeconomically unequal legacies of apartheid.